2005
DOI: 10.1051/apido:2005032
|View full text |Cite
|
Sign up to set email alerts
|

Assessing delayed and acute toxicity of five formulated fungicides to Osmia lignaria Say and Apis mellifera

Abstract: -The delayed and acute toxicity of benomyl (Benlate), captan (Captan 50WP), iprodione (Rovral), propiconazole (Orbit), and neem oil (Trilogy) to two crop pollinators, A. mellifera and O. lignaria, was evaluated. Survival after contact and oral single exposure to high doses of the pesticides was compared to survival of controls with the dosing vehicle. LD 50 values at 24, 48 and 72 h from exposure were determined. Contact and oral exposure to benomyl and iprodione did not affect survival of any of the two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 22 publications
2
70
4
Order By: Relevance
“…While our study shows that bee toxicities based on honeybees can be predictive of field effects on wild bee communities, mechanistic understanding of pesticide risk to wild bee communities requires small-scale, manipulative toxicity tests on solitary bee species [27,63]. The few such studies on solitary bees reveal that some fungicides can be acutely and chronically toxic to solitary mason bees (Osmia lignaria Say) [25,64] and supports speciesspecific toxic thresholds among bees. Fungicides alone may have low toxicity, but they may interact with other pesticides or with 'inactive' ingredients, often included in spray formulations, to produce synergistically toxic effects [56,57].…”
Section: Discussionmentioning
confidence: 67%
“…While our study shows that bee toxicities based on honeybees can be predictive of field effects on wild bee communities, mechanistic understanding of pesticide risk to wild bee communities requires small-scale, manipulative toxicity tests on solitary bee species [27,63]. The few such studies on solitary bees reveal that some fungicides can be acutely and chronically toxic to solitary mason bees (Osmia lignaria Say) [25,64] and supports speciesspecific toxic thresholds among bees. Fungicides alone may have low toxicity, but they may interact with other pesticides or with 'inactive' ingredients, often included in spray formulations, to produce synergistically toxic effects [56,57].…”
Section: Discussionmentioning
confidence: 67%
“…Ladurner et al (2005) demonstrated an effect of certain fungicides by directly applying these substances to O. lignaria. In addition, they observed effects of spraying on foraging and nesting behavior, but could not demonstrate an effect under caged conditions (Ladurner et al 2008).…”
Section: Dispersalmentioning
confidence: 99%
“…Iprodione was found to be non-toxic to honeybees and Osmia lignaria (a solitary bee) after direct contact and oral exposure (Ladurner et al 2005). Fungicides may affect bees indirectly by reducing the populations of fungi that are beneficial to bees.…”
Section: Pesticidementioning
confidence: 99%